Public-private partnership and economic growth in Morocco: An empirical análisis - Loukili, Zineb; El Hamma, Azzouz (European Scientific Journal, ESJ, 2024)
Public-private partnerships (PPPs) have emerged as an innovative investment model for infrastructure projects. Introduced in Morocco during the 1990s, PPPs have since become an important element of the country’s economic development strategy, in order to stimulate economic development and address infrastructure challenges. Our paper aims to study the impact of investment in public-private partnerships on economic growth. This study serves to enrich and complement the existing work in this field, thus contributing to the advancement of knowledge and expanding the boundaries of the existing literature. The study uses a time-series dataset from Morocco that includes PPP investments, the number of PPPs, GDP, and other control variables between 1990 and 2020. The dataset was analyzed using the multiple linear regression method. Results indicate that investment in PPPs has a positive and statistically significant impact on Morocco’s economic growth, underscoring the effectiveness of this investment model in the national context.